Progressive Collapse of Structural Systems Considering Force and Corrosion Damage - S. I. Merkulov (Железобетонные конструкции)
The main directions of development of the theory of structural safety of buildings and structures have been formulated. A hierarchical approach to the assessment of structural safety of objects under corrosion damage from structural materials to structural system is proposed. Peculiarities of corrosion damageability of concrete of reinforced concrete structures are determined, mechanisms of force and corrosion effects and their influence on progressive destruction of structural systems of exploited buildings are analyzed.